Green practices in hotel industry: factors influencing the implementation / Fauziah Deraman…[et al.] - Deraman, Fauziah; Ismail, Noralisa; Mod Arifin, Ahmad Izzat; Mostafa, Mohamad Izzuan Azhar (Faculty of Hotel and Management, UnIversiti Teknologi MARA, Selangor, Puncak Alam Campus, 2017)
There has been a tremendous effort in creating awareness and to increase the number of establishments with green practices in hotel industry. This is due to undeniable negative environmental impacts derived from hotel activities. Therefore, hotels are grabbing this opportunity to preserve the environment and at the same time, they are reaping benefits from the green practices. However, despite the promising benefits they may gain, the hotels’ participation in green practices are still low due to several factors that influenced the hotels whether to implement the green practices or remain with the current operational practices. Thus, the aim of this study is to determine the influencing factors toward the implementation of green practices in hotels and to identify the most influencing among all factors. Three factors were identified, which were cost, consumers’ support, and employees’ support. Details regarding these three factors had been discussed by previous researchers. As a result, consumers’ support had been identified as the most influencing factor towards the implementation of green practices in hotel.